Pos Express Delivery Services in Manado City Using Servqual Method - Angmalisang, Stefani Irene; Londa, Marlyn T. (AIBPM Publisher, 2022)
This study aims to measure the level of quality of Pos Express delivery services in Manado city during the pandemic of Covid19. The study using Servqual theory measurement method by Parasuraman (1985), by distributing questionnaires to consumers. Its asking their expectations and perceptions about the quality of Pos Express services in Manado city, then calculating the difference between both. The results show the magnitude of service quality. The research sample is 100 respondents, who have met the research requirements, which is at least 2 times using these services. The results obtained are the overall servqual value is -0.31, meaning that the quality of Pos Express services in Manado city still does not meet consumer expectations.